The Crowdfunding during Masamba Natural Disaster - Biliam, Vivian; Ariestya, Angga (Jurnal Komunikasi Profesional, 2024)
The ability of crowdfunding owners to increase public participation in disseminating information through social media is one of the success factors of crowdfunding. While dissemination of information through social media is a form of Electronic Word-of-Mouth (e-WOM). This study’s primary objective was to determine whether e-WOM about crowdfunding for Masamba can directly affect donation intention or should be mediated by the attitude towards donation. This study used a quantitative approach by distributing questionnaires to 332 respondents who met the criteria. The study found that there was a positive and significant direct effect between e-WOM about crowdfunding for Masamba and donation intention. Meanwhile, the attitude towards donation also mediates the effect of e-WOM about crowdfunding for Masamba on donation intention. This study also provides new insights for communication that combine mass communications and new communication media, especially social media.